Pemberdayaan Masyarakat Dalam Pengembangan Industri Rumah Tangga Keripik Singkong Di Desa Sungai Majo Pusako - Yelly Zamaya; Sri Endang Kornita; Taryono; Eriyati (Journal of Community Engagement Research for Sustainability, 2022)
Community empowerment activities are a process of community participation or involvement in carrying out an activity that can improve the standard of living, both socially, culturally and economically. Community empowerment activities focus on developing the cassava chip home industry in Sungai Majo Pusako Village. This community empowerment activity aims to provide information and understanding to the public that the addition of flavor variants, packaging and marketing techniques based on information technology can increase sales and income. This activity was carried out by the Service Team, namely lecturers and the Kukerta Balek Kampung group in Sungai Majo Pusako Village, Kubu Babussalam District, Rokan Hilir Regency, Riau Province. This empowerment activity is carried out by providing information about new flavor variants that are suitable for cassava chips, socializing about the importance of packaging, and online marketing techniques. The result of this empowerment activity is an increase in public knowledge about new flavor variants, the importance of packaging and online marketing techniques. After this empowerment activity is carried out, it is hoped that the community will continue to develop their favorite flavor variants, more attractive packaging designs, and information technology-based marketing techniques.